The Effect of Company Size and Audit Committee on Tax Aggressiveness with Profitability as Moderating Variables - Ratih Qadarti Anjilni; Sri Putri Winingrum WA (Universitas Pamulang, 2022)
This study examines the effect of Company size and audit committee on tax aggressiveness with profitability as a moderating variable. The research was conducted on the property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2016-2020. The sample selection technique used in this research is the purposive sampling technique. The sample in this study was 35 companies with a number of objects of observation as many as 175 annual reports. The results show that Company size and audit committee have a significant negative effect on tax aggressiveness, Company size and audit committee simultaneously have a significant effect on tax aggressiveness, and profitability as a moderating variable has a significant positive effect on the relationship between Company size and tax aggressiveness, profitability as a moderating variable significant positive effect on the relationship between the audit committee and tax aggressiveness. The contribution of this research, it is hoped that this research can provide motivation and strategies in decision making before implementing tax avoidance which is classified as aggressively applied by property and real estate companies by doing tax avoidance that does not violate tax regulations